Promosi Media Online dalam Mengatasi Persaingan Bisnis di Era Digital Pada Portal Berita Koranmandala.com - Fadillah, Annisa Nur (Jayapangus Press, 2025)
The number of online media in Indonesia today makes the competition for information production tighter in the digital media industry so that attractive marketing strategies must be carried out by media company owners. Koranmandala.com is a regional media, especially in the Bandung and surrounding areas, so it competes with other news portals such as AyoBandung.com, Koran Gala, Galamedia and others. The purpose of this study is to determine the promotion mix used by Koranmandala.com in facing business competition among other online media. The method used is qualitative with an explanatory case study approach and data collection through in-depth interviews, documentation and observation. While the concept in this study uses promotional tools in the form of advertising, sales promotion, public relations, and direct & digital marketing. Network Society theory is used in this research as an analysis knife. The results of this study are that it is found that the promotional strategy carried out by Koranmandala.com has a significant impact on increasing engagement ratings along with insights on social media, besides increasing brand awareness, news easily read by Google and included in FYP and increasing the number of followers. As for the program implemented by Koranmandala.com, it generates advertising and sponsorship income, forms a positive brand image and provides motivation so that it changes the attitude and behavior of someone watching the program. Meanwhile, advertising on social media with free advertising techniques, bundle packages and using pick-up procedures can provide high brand awareness and a wide audience reach. The conclusion in this study is that the use of promotional tools applied by Koranmandala.com is running well so that it can increase brand awareness, generate significant revenue, increase engagement and social media insight to change audience attitudes.